1999
DOI: 10.1093/nar/27.3.839
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed mRNAs in human fetal liver across gestation

Abstract: Differential gene expression, with its precise start and stop times, is believed to be critical for the programmed development of new cells and tissues. Within the developing fetus, one tissue of particular interest is fetal liver. This organ undergoes rapid changes in the pathway toward liver development in utero since it is also the major site of hematopoiesis, until bone marrow hematopoiesis predominates. Believing that patterns would emerge from the bi-weekly large-scale inspection of expressed genes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 30 publications
0
37
0
1
Order By: Relevance
“…This may suggest that MAC30 is one of the developmentally regulated proteins that are expressed in the hematopoietic development (2). MAC30 was first described to be overexpressed in meningiomas, and altered expression was also found in different types of human tumors (1)(2)(3). MAC30 is expressed at moderate levels in normal pancreatic acinar cells, strongly present in tubular complexes of chronic pancreatitis, and observed at low levels in most pancreatic cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…This may suggest that MAC30 is one of the developmentally regulated proteins that are expressed in the hematopoietic development (2). MAC30 was first described to be overexpressed in meningiomas, and altered expression was also found in different types of human tumors (1)(2)(3). MAC30 is expressed at moderate levels in normal pancreatic acinar cells, strongly present in tubular complexes of chronic pancreatitis, and observed at low levels in most pancreatic cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…14 In addition, hepatoblasts express ␣-fetoprotein (AFP), insulin-like growth factor-2 (IGF), IGF-binding proteins, and some ribosomal proteins not expressed by hepatocytes. 15 Hepatocytic maturation is marked by the expression of a number of genes, proteases (eg, cathepsin L), acute phase proteins (eg, orosomucoid), enzymes involved in the metabolism of nucleotide intermediates (eg, nicotinamide methyl-transferase), of glucids (eg, glucose-6-phosphatase), and of amino acids (eg, tyrosine-aminotransferase) characteristic of the different liver metabolic functions. 15,16 Finally, many proteins, such as cytokeratins 8 and 18 and albumin, expressed by hepatoblasts continue to be expressed by hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…15 Hepatocytic maturation is marked by the expression of a number of genes, proteases (eg, cathepsin L), acute phase proteins (eg, orosomucoid), enzymes involved in the metabolism of nucleotide intermediates (eg, nicotinamide methyl-transferase), of glucids (eg, glucose-6-phosphatase), and of amino acids (eg, tyrosine-aminotransferase) characteristic of the different liver metabolic functions. 15,16 Finally, many proteins, such as cytokeratins 8 and 18 and albumin, expressed by hepatoblasts continue to be expressed by hepatocytes. 13,15 In many respects, hepatoblasts appear similar to oval cells proliferating in response to liver damage.…”
Section: Introductionmentioning
confidence: 99%
“…To date several studies have reported that the imprinted Igf2 [20][21][22][23][24] and Dlk1 [18,19,25] genes are involved in the development of fetal liver hematopoiesis. During the first half of the embryonic period, the space between the hepatic cell cords Igf2 and Dlk1 expression were quantitatively analyzed by realtime PCR.…”
Section: Discussionmentioning
confidence: 99%